Staphylococci that carry the nuc gene - Andrade, NPC (2017)
Inflammation of the mammary gland, known as mastitis, is a serious problem, because it is responsible for the decrease in milk yield and quality. Bacteria of the species Staphylococcus aureus, causing intramammary infections in small ruminants, are often isolated from milk samples and frequently resistant to antimicrobials. The thermostable nuclease encoded by the nuc gene is a virulence factor, as it promotes evasion of neutrophil extracellular traps (NETs), which are networks of DNA strands with antimicrobial proteins. The nuc gene is present in most S. aureus, however some isolates not carrying this gene have been described. Moreover, the nuc gene has also been detected in other Staphylococcus species, notably in S. intermedius, S. hyicus and S. simulans. The aim of this study was to assess the presence of the nuc gene in staphylococci isolated from goat and sheep milk samples. Three hundred and sixty-eight samples of milk were collected, from 187 animals, belonging to six flocks in Alentejo. Ninety-one isolates of the genus Staphylococcus were identified by classical biochemical methods and through the VITEK2 microbial identification system (BioMérieux, France). The presence of the nuc gene was assessed by PCR. The reference strain S. aureus ATCC 25923 was used as positive control. According to VITEK2, 24 S. caprae, 13 S. epidermidis, 13 S. chromogenes, 11 S. aureus, nine S. simulans, five S. warneri, five S. lentus, four S. capitis, four S. haemolyticus, one S. auricularis, one S. hominis spp. hominis and one Staphylococcus spp. (not identified to species level) were identified. Twenty-three out of the 91 isolates (25.3%) carry the nuc gene. With the pair of primers used, this gene was detected in seven different Staphylococcus species: 10 S. aureus (43.5%), three S. warneri (13%), three S. lentus (13%), two S. caprae (8.7%), two S. epidermidis (8.7%), two S. chromogenes (8.7%) and one S. capitis (4.3%). Furthermore, the nuc gene was not detected in one S. aureus isolate. We suggest that the presence/absence of the nuc gene is not a reliable method for the identification of S. aureus and that this virulence factor may be involved in small ruminant mastitis pathophysiology.